Landscape scale thermoregulatory costs from sublethal exposure to Deep Water Horizon oil in the double-crested cormorant. (March 2020) - Dorr, Brian S.; Mathewson, Paul D.; Hanson-Dorr, Katie C.; Healy, Katherine A.; Horak, Katherine E.; Porter, Warren
Abstract: Toxic effects of heavy oiling to wildlife are well known from oil spills, although sublethal oil exposure effects are poorly understood. We used Niche Mapper™, to compute spatially and temporally specific energetic and behavioral impacts of repeated sublethal oil exposure to double-crested cormorants ( Phalacrocorax auritus ). During winter (October–March) cormorants exposed to 13 g, 39 g, and 65–78 g of oil, had on average a 31%, 59%, and 76% predicted increase in total resting energetic requirements (RMR) compared to unoiled birds, respectively. Increased RMR resulted in a mean (±SD) predicted increase in time spent foraging of 36 (±13) min·d − 1 . During the breeding season (April–September), cormorants had on average a 29%, 57% and 73% increase in total RMR and the mean predicted increase in time spent foraging was 131 (±49) min·d − 1 . Thermoregulatory effects of sublethal oil exposure may cause greater impacts to bird populations than is currently understood. Highlights: Modeled spatially and temporally specific energetic effects of sublethal oil exposure for a bird Increase in thermoregulatory costs of up to 165% of resting metabolic rate Increases in thermoregulatory cost could increase foraging related activities up to 6.3 h/d. Sublethal oil exposure may cause greater impacts to birds than previously considered.